Os significados de uma visita a um observatório astronômico: um estudo baseado nas memórias e emoções de estudantes - Fernando Roberto da Costa Linhares (2019)
This research has as main objective to understand meanings that a group of visitors attributes to the school visits that they carried out to the Frei Rosario Astronomical Observatory, by means of stimulus to their long-term autobiographical memory and possible emotional traits present in their speeches. We start from the hypothesis that activities considered as non-formal education, such as school field trips, are pedagogical resources with the potential to mean much more than a class out, with the capacity to allow visitors affective impacts, even after many years of visit. From an initial set of 1,971 registration forms filled out by students from seven educational institutions that visited the astronomical observatory between 1998 and 2008, it was possible to identify and compose a sample of visitors. From this sample, we collected information through online questionnaires of 90 respondents and conducted semistructured interviews with 12 youngsters, aged between 25 and 35 years old, applying the stimulated recall method. The informations was analyzed, in a qualitative research approach and with the use of content and discourse analysis techniques. Among the obtained results, we emphasize that the participants have vivid memories about the episode of the visit, especially in relation to the place and the activities performed. Once the students reflected on the visit, we identified that their memories referred to some of the emotions felt at the time, such as the excitement of knowing a place considered new and different; the astonishment and wonder at the visual images, which include the local landscape, the size of the telescope, and the sky free of light pollution; and also the feelings of disappointment when the observed images of the planets didnt meet their expectations, and frustration when the meteorological conditions didnt allow the realization of astronomical observations. We conclude that Frei Rosario Astronomical Observatory fulfills an important educational role in the dissemination of Astronomy, because using resources that attract attention, stimulates students' curiosity and interest, and makes the experience memorable, meaningful and integrated to the identity of the visitors.